2016
DOI: 10.1073/pnas.1600958113
|View full text |Cite
|
Sign up to set email alerts
|

Development of the turtle plastron, the order-defining skeletal structure

Abstract: The dorsal and ventral aspects of the turtle shell, the carapace and the plastron, are developmentally different entities. The carapace contains axial endochondral skeletal elements and exoskeletal dermal bones. The exoskeletal plastron is found in all extant and extinct species of crown turtles found to date and is synaptomorphic of the order Testudines. However, paleontological reconstructed transition forms lack a fully developed carapace and show a progression of bony elements ancestral to the plastron. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 61 publications
1
34
0
1
Order By: Relevance
“…Rice et al . () demonstrated that the relative position and timing of the plastral condensations indeed matches those of the precursors of the sternal cartilages in birds and mice. However, the condensations in the ventral mesenchyme of turtle embryos commit to bone formation and hence suppress the development of sternal cartilages.…”
Section: Plastronmentioning
confidence: 89%
See 1 more Smart Citation
“…Rice et al . () demonstrated that the relative position and timing of the plastral condensations indeed matches those of the precursors of the sternal cartilages in birds and mice. However, the condensations in the ventral mesenchyme of turtle embryos commit to bone formation and hence suppress the development of sternal cartilages.…”
Section: Plastronmentioning
confidence: 89%
“…It is interesting to note that ossification of the carapace lags behind that of the plastron in extant turtles (Rieppel ) even though the onset of the ontogenetic development of both halves of the turtle shell coincides (Rice et al . ). Clark et al .…”
Section: Plastronmentioning
confidence: 97%
“…In the second example, researchers might want to provide more insight into the development of the carapace in the Angulate tortoise, Chersina angulate (e.g. Rice et al 2016).…”
Section: T O W a R D S A G E N E R A L F R A M E W O R K F O R I N V mentioning
confidence: 99%
“…Even though a less detailed scenario is currently known for the morphological and developmental origins of the plastron, recent research presented important advancements (Cherepanov 1997;Cebra-Thomas et al 2007Rice et al 2016). Most extant turtles possess nine bones in the plastron (Zangerl 1969), but stem-turtles, e.g.…”
Section: Turtles As Models Of Vertebrate Evolutionmentioning
confidence: 99%
“…From those, the three anterior plates, the epiplastra and entoplastron, are thought to be derived from the clavicles and interclavicles, respectively (Cherepanov 1997;Lyson et al 2013) and the posterior plates have been associated with modified paired abdominal ribs, the gastralia (Romer 1956;Gaffney 1990;Kuratani et al 2011), even though a distinct type of ossification (forming bone spicules) is characteristic of plastral bones (Rice et al 2016). It has been shown that those plates have an important contribution from neural crest cells (Cebra-Thomas et al 2007Gilbert et al 2007) and that their appearance suppresses the development of a sternum in the ventral part of the embryonic turtle body and is concomitant with that of the carapacial ridge (Rice et al 2016). Thus, albeit more work needs to be done to better understand the nature of the plastron, its appearance also seems to be related to the evolutionary novelty of turtles, the carapacial ridge (Kuratani et al 2011).…”
Section: Turtles As Models Of Vertebrate Evolutionmentioning
confidence: 99%